تأثير نمط الاستناد الرئيسي على التصميم الأمثل لجائز I نظامي وملفوف على البارد تناظرياً تحت تأثير حمولة موزعة بانتظام - سعيد محمود; حيدر بادية (Latakia University Journal -Engineering Sciences Series, 2019)
In this paper we present a modern treatment of the optimum design procedure for a cold formed mono-symmetrical I beam under the action of uniformly distributed load. This problem is highly governed by different kinds of buckling constraints. As the walls of this beam are very thin, we will consider the design constraint of the global lateral buckling in addition to the design constraints related to the local buckling of the flanges and the web. This constraint will be established for four cases of vertical support conditions and only one case of lateral support condition, and as these two groups of support conditions could be practically independent, we suppose that the shape of the lateral buckling is not altered by the vertical displacement shape. Then, we investigate the influence of the vertical displacement boundary conditions dictated by the type of the vertical supports on the values of the critical lateral buckling load. The other constraints of the problem are related to the fabrication processes. This optimum design problem will be solved using a Genetic Algorithm program implemented using MATLAB. The test of this program constitutes an essential part of this paper. نقدم في هذه المقالة مسألة التصميم الإنشائي الأمثل لجائز I نظامي وملفوف على البارد تناظرياً تحت تأثير حمولة موزعة بانتظام. تتأثر هذه المسألة بأشكال متنوعة من التحنيب (عدم الاستقرار) وذلك بسبب قلة سماكة الصفيحة المشكلة للمقطع. بالإضافة إلى قيود التصميم المتعلقة بالتحنيب الموضعي للجناحين وللجسد، سنأخذ بعين الاعتبار قيد تصميم متعلق بالتحنيب الكلي الجانبي. سنستنتج عبارة هذا القيد لأربع حالات من أنماط الاستناد الشاقولي ولنمط واحد من الاستناد الجانبي. وبما أن هذين النمطين مستقلان عملياً، سنفترض أن شكل نمط التحنيب الجانبي ثابت ولا يتأثر بشكل الانتقال الشاقولي، ثم سندرس تأثير شروط الانتقال الشاقولي الطرفية على قيم حمولة التحنيب الكلي الجانبي الحرجة. أما بقية قيود التصميم فهي متعلقة بآلية تشكيل المقطع. وستحل مسألة التصميم الأمثل الناتجة باستخدام خوارزمية جينية سيتم في هذه المقالة استعراض نتائجها واختبارها.